Impact of instructional supervision on skills acquisition and job creation tendency among students in public secondary schools in Calabar Metropolis: Implication for economic recovery (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
Youth unemployment in Nigeria has increased significantly in recent times resulting in increased frustration and crime. Cross River State being a centre of tourism in Nigeria has a number of unemployed youths. Among them are graduates of secondary schools who lack the skills to explore opportunities in their immediate environment, become job creators instead of chasing scarce white collar jobs. This is an indication that secondary education established to among other things equip students with skills for survival, has not been fully attained. It is against this background that this study investigated the Impact of Instructional Supervision on Skills Acquisition and Job Creation Tendency among Students in Public Secondary Schools in Calabar Metropolis: Implication for Economic Recovery. Two research questions and two null hypotheses guided the study. Ex-post facto design was adopted for study. The population was 4,379 students while 500 students were sampled for the study using purposive sampling technique. Data collection was done using a 30-items questionnaire titled “Instructional Supervision, Skills Acquisition and Job Creation Tendency Questionnaire (ISSAJCTQ).” Its validation was determined by experts in Educational Management, and Test Measurement and Evaluation, while its reliability was established using Cronbach alpha technique with a coefficient range of 82, .86, and .89, respectively. Simple linear regression was employed in testing the null hypothesis at 0.05 level of significance and 480 degree of freedom. The findings of the study revealed that instructional supervision have a significant impact on skills acquisition and job creation tendency among students in public secondary schools in secondary schools in Calabar metropolis, Cross River State, Nigeria. It was recommended among others that teachers should engage in professional development opportunities to enhance their instructional delivery, and guide the students in acquiring useful skills for self reliance and job creation.
Keywords: Instructional Supervision; Skills Acquisition; Job Creation; Economic Recovery